Application of fuzzy optimisation in forecasting and planning of construction industry - Vasant, P.; Barsoum, Nader; Kahraman, C.; Dimirovski, G. (Idea Group, 2008)
This chapter proposes a new method to obtain optimal solution using satisfactory approach in uncertain environment. The optimal solution is obtained by using possibilistic linear programming approach and intelligent computing by MATLAB?. The optimal solution for profit function, index quality and worker satisfaction index in construction industry is considered. Decision maker and implementer tabulate the final possibilistic and realistic outcome for objective functions respect to level of satisfaction and vagueness for forecasting and planning. When the decision maker finds the optimum parameters with acceptable degree of satisfaction, he/she can apply the confidence of gaining much profit in terms of helping the public with high quality and least cost products. The proposed fuzzy membership function allows the implementer to find a better arrangement for the equipments in the production line to fulfill the wanted products in an optimum way.